Active Video Games Performance and Heart Rate on the Wii or Kinect in Children with and without Developmental Coordination Disorder - Jorge Lopes Cavalcante-Neto; Dorothee Jelsma; Tatiane Targino Gomes Draghi; Eloisa Tudella; Bouwien Smits-Engelsman (Children, 2022)
Our objective was to compare changes in game performance and intensity of heart rate (HR) between two types of active video game (AVG) in children with and without Developmental Coordination Disorder (DCD). Additionally, we assessed the level of improvement per game as well as the perceived exertion and enjoyment during training. Seventy-six children, 36 with DCD and 40 without (TD) were randomly assigned to a 5-week program of Wii-Fit or Xbox-Kinect training 2× a week. The steepness of the performance curves was not different between consoles, nor between groups. Playing Kinect games resulted in higher HR in both groups. Wii and Kinect seem to be comparable AVG consoles that can be used for children with and without DCD, with the Kinect reaching a higher intensity of training.